The Application of Natural Law Theory in Resolving Cases of Business Ethics Violations: A Review of the Principles of Justice and Morality - Rahmawati Rahmawati; Abdul Mujib (LEGAL BRIEF, 2025)
This article examines violations of business ethics that frequently arise in the corporate world, when corporate decisions cannot be resolved solely through positive law because they involve moral issues such as dishonesty, worker exploitation, and environmental damage. Natural law theory is offered as a fairer and more moral approach to addressing these issues. The purpose of this research is to analyze how the principles of justice and morality in natural law can be used as substantive solutions to business ethics disputes. The method used is normative juridical, through a review of relevant regulations, doctrines, and legal literature. The conclusion of this study shows that the application of natural law theory in resolving business ethics violations offers a fairer and more humanistic approach compared to positive law, which tends to be procedural. Natural law provides a strong moral foundation, encouraging companies to consider social and environmental impacts in decision-making. Thus, the integration of natural law principles can enrich the existing legal framework with more substantial justice values. The renewal of this research lies in developing an understanding of the integration of natural law within the existing legal system, particularly regarding business ethics violations. This approach provides a more inclusive and sustainable solution, and opens up space for legal reform that is more adaptive to social and moral changes. This research also contributes to the development of natural law theory in the increasingly complex global business world.